Peradaban Dan Pemikiran Islam Pada Masa Dinasti Fathimiyah - Himmatul Fitriah (Islam & Contemporary Issues, 2021)
History hasirecorded how theiexistence of the Fatimididynasty to today holdsimany very interestingistories. Not onlyithat, Islamic cultureiis growing rapidly. Theiproof can be seen from theiestablishment of the Al-AzhariMosque which servesias a center for Islamic studies andiscience.The progressiof the scientific field ofithe Fatimid dynasty canialso be proven throughithe existence of DaruliHikam or Darul Ilmu alsoicontributed greatly toithe development ofiIslamic civilization andiintellectuals. Not onlyiscience, the Fatimididynasty also achievediiprosperity in theinfields ofiipolitics, education, economiciiscience and technology, trade, socialiand religiousiaffairs. Therefore, thisiarticle will Trying toire-discover the earlyihistory of the emergenceiof the Fatimididynasty, the Caliphs ofithe Fatimid dynasty, theiperiod of progressiand decline of the Fatimididynasty and theiinfrastructure of theiFatimid dynasty.